Secured Restaurant Reservation System - Hishamudin, Nur Hanis; Abdullah, Nurul Azma (Applied Information Technology And Computer Science, 2022)
Restaurant reservation system is a pre-arranged plan to have a table at a restaurant available. The system assists the owner in ensuring the available table and reserved table do not overlap and meals can be prepared in time. However, the existing system might have unauthorized access and fraudulent activities which lead to information theft. Hence, the developed system which is Secured Restaurant Reservation System solved the concerns highlighted earlier. The system used a password policy for sign in, two-factor authentication and access control to prevent unauthorized access to the system. The system uses Prototype Model with PHP programming language. As a result, the system prioritized the confidentiality and integrity concepts by limit unauthorized access to the database of the system.